AP-1 and the injury response of the GFAP gene - Brenner, Michael (J Neurosci Res, 2018)
Increased GFAP gene expression is a common feature of CNS injury, resulting in its use as a reporter to investigate mechanisms producing gliosis. AP-1 transcription factors are among those proposed to participate in mediating the reactive response. Prior studies found a consensus AP-1 binding site in the GFAP promoter to be essential for activity of reporter constructs transfected into cultured cells, but to have little to no effect on basal transgene expression in mice. Since cultured astrocytes display some properties of reactive astrocytes, these findings suggested that AP-1 transcription factors are critical for the upregulation of GFAP in injury, but not for its resting level of expression. We have examined this possibility by comparing the injury response in mice of lacZ transgenes driven by human GFAP promoters that contain the wild type AP-1 binding site to those in which the site is mutated. An intact AP-1 site was found critical for a GFAP promoter response to the three different injury models used: physical trauma produced by cryoinjury, seizures produced by kainic acid, and chronic gliosis produced in an Alexander disease model. An unexpected additional finding was that the responses of the lacZ transgenes driven by the wild type promoters were substantially less than that of the endogenous mouse GFAP gene. This suggests that the GFAP gene has previously unrecognized injury-responsive elements that reside further upstream of the transcription start site than the 2.2 kb present in the GFAP promoter segments used here.